A possible easy way to predict response to cardiac resynchronization therapy: The role of QRS Index - Giuseppe Coppola; Cristina Madaudo; Amedeo Prezioso; Enrico Bonnì; Giuseppina Novo; Vincenzo Sucato; Gianfranco Ciaramitaro; Alfredo Ruggero Galassi; Egle Corrado (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2023)
Background: Some studies have evaluated the role of QRS duration (QRSd) as predictor of response to Cardiac Resynchronization Therapy (CRT). However, their results are still not entirely clear. The goal of our study was to determine the correlation between the relative change in QRS narrowing index (QI) compared to clinical outcome and prognosis in patients who underwent CRT implantation. Methods: We collected clinical and echocardiographic data of 115 patients in whome a CRT device was implanted in accordance with current guidelines. QRS duration before and after CRT implantation and QI were measured.  Results: After 6 months, a significant improvement in all echocardiographic parameters was detected. QI was correlated to reverse remodelling (r = +0.19; 95% CI: 0.006 to 0.35, p = 0,049). The value of QI that predicted best LV reverse remodelling after 6 months of CRT was 12.25% (sensitivity = 65,5%, specificity = 75%, area under the curve = 0.737, p = 0,001). Independent predictors of QI are sex, serum creatinine and eGFR measured at baseline and LVEF pre-CRT performed by echocardiography. We observed an betterment in their HF clinical composite score and NYHA class at 12 months.  We have also investigated the clinical outcomes and the possible sex differences related to QI. Conclusions: Patients with a larger QI after CRT initiation showed greater echocardiographic reverse remodelling and better outcome from death or cardiovascular hospitalization. QI seems to be an easy-to- measure variable that could be used or evaluated to predict CRT response but further studies are needed.